Upaya Meningkatkan Kepercayaan Diri melalui Layanan Bimbingan Kelompok pada Siswa Kelas X1 - Dewi, Nunur Yuliana; Supriyo, Supriyo; Saraswati, Sinta (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
This study aims to determine the efforts and success in increasing self-confidence through group guidance services to students class X1 in SMA 1 state Sumber Rembang. This type of research is action research. The research sample using purporsive sampling are 10 students who have self-confidence low, medium and high. Data collection methods used were psychological scales and observation. The data analysis technique used is obtained using the Wilcoxon test t count = 55> t table = 8. The results obtained, before getting group guidance services whose members have high self-confidence 81%, members who have medium self-confidence was 64%, while members who have low self-confidence 53%. After receiving group guidance services self-confidence increased student, members of which have a high self-confidence increased 83% in the category of a high percentage, members who have medium self-confidence increased 74% in the category of a high percentage of self-confidence, and members who have low self-confidence increases 69% in the category of percentage of high self-confidence. It was concluded that self-confidence in learning Indonesian can be improved through group guidance services.